Analysis of The Influence of Studying at Home Due To The Covid-19 District Towards Academic Achievements Of Students STIkes Panti Waluya Malang - Sr. Felisitas A Sri; Monika Luhung; Devanus Lahardo (Jurnal Keperawatan Malang, 2020)
Background: Covid-19 disease outbreak has brought urgent changes to various sectors, one of which is the education sector. A new policy also occurs in the world of education to change learning from a learning in a room or a building be a learning at home. Student academic achievement is influenced by several factors such as the number of hours of study per day, environment, learning motivation and quality of teaching. By knowing the dominant factor is expected to be able to improve student academic achievement. Purpose: This study aims to determine the influence of what factors influence academic achievement during study from home (SFH) on students of STIKes Panti Waluya Malang. Methods: This study used a survey of 38 students to collect primary data. The data were processed by multiple linear regression analysis. Results: This study shows that there is a relationship between learning motivation, length of study, quality of teaching and environmental factors on the academic achievement of students at STIKes Panti Waluya Malang (Sig <0.05). Conclusion: The factors that influence academic achievement are the length of study and the quality of learning. The regression coefficient for the length of study variable is 0.086 and the regression coefficient for the quality of learning is 0.039. The dominant factor is the length of study and then the quality of learning